ANALYSIS OF THE EFFECT OF BIOSOLAR FUEL AND PERTAMINA DEX ON POWER PERFORMANCE, TORQUE, AND DIESEL ENGINE FUEL CONSUMPTION - Dandung Rudy Hartana; Haryanto Haryanto; Wahid Anwar (TRAKSI, 2023)
The fuel used in the engine significantly affects the engine's performance, so there is an improvement in the fuel quality from time to time. Especially for diesel motors, which initially only used diesel, have now been developed, namely biodiesel and Pertamina dex. For this reason, the performance testing of the diesel engine type 4JA1 was carried out using Pertamina dex and biodiesel fuels in the combustion engine laboratory of the Yogyakarta National Institute of Technology so that the performance parameters for each fuel were obtained. This study uses an experimental method with four engine speed variations, namely 1000 rpm, 2000 rpm, 2500 rpm, and 2500 rpm. The tool used in this study is a diesel engine type 4JA1 connected to a dynamometer to test the diesel engine's performance. The diesel engine's performance analyzed in this test is power, torque, and specific fuel consumption. The results showed that fuel-type materials significantly affect the performance of the resulting engine. Overall engine performance using Pertamina dex fuel is superior to biodiesel. Pertamina dex fuel performance generated power: 3,938 kW, 7,569 kW, 12,800 kW, 18,046 kW; torque 37,632 Nm, 48,216 Nm, 61.152 Nm, 68,992 Nm; fuel consumption 0.666 Kg/kWh, 0.647 kg/kWh, 0.511 kg/kWh, 0.262 kg/Kwh. Performance biodiesel fuel produced 2.854 kW, 6.954 kW, 9.518 kW, 11.795 kW; torque 27,273 Nm, 44,296 Nm, 45,472 Nm, 45,08 Nm; fuel consumption is 0.908 kg/kWh, 0.533 kg/kWh, 0.503 kg/kWh, 0.394 kg/kWh.